The risk of professionalization of social work in Spain - Hernández Echegaray, Arantxa (Cuadernos de Trabajo Social, 2018)
This article relates de-professionalization theory to the current state of social work in Spain. De-professionalization refers to the process of erosion of the monopoly on knowledge as a consequence of loss of professional autonomy and authority. The conceptual elements of this theory are applied to social work and five factors that impact on the de-professionalization process are studied: a) the policy of precariousness in the provision of social services; b) the increasing precariousness of the job market; c) the bureaucratization of the professional field and activity; d) the codification and standardization of intervention; and e) fragmentation of the knowledge process. Bases are established to comprehend the risks that social work faces as a profession, and professional autonomy is emphasized from the perspective of ethics and reinforcement of scientific foundations.
Keywords: social work; de-professionalization; precariousness; bureaucracy; standardization.